TINJAUAN BIAYA DAN WAKTU PADA PROYEK PEMBANGUNAN GEDUNG PERPUSTAKAAN DAN ARSIP DAERAH KEC. SUKADANA - Yahya, -; Rafie, -; Syahrudin, - (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2016)
A project implementation should meet three criteria, namely the cost of the project, quality of work and job completion time. If the project costs less, there will be many obstacles, such as the quality of the work is less than the prescribed standards, hampered the work time, and so on. There are so many factors that should be reviewed in determining the costs should be provided, such as the type of activities that will be carried out in a project, the cost or unit price of an activity, the level of activity, the price of materials needed, the price of wages, and the like. The purpose of this final project was to determine the magnitude of the budget on the project and know the duration or length of time to work there. The amount of budget costs involved in building projects the District Library and Regional Archives Sukadana is Rp. 3,784,526,300, -. The length of time the work on the project is 138 days. Â Keywords: Project, Labor, Time, Cost, Prices